Replication of Dengue Virus in K562-Megakaryocytes Induces Suppression in the Accumulation of Reactive Oxygen Species - Kaur, Jaskaran; Rawat, Yogita; Sood, Vikas; Periwal, Neha; Rathore, Deepak Kumar; Kumar, Shrikant; Kumar, Niraj; Bhattacharyya, Sankar (Frontiers in Microbiology, 2022)
Dengue virus can infect human megakaryocytes leading to decreased platelet biogenesis. In this article, we report a study of Dengue replication in human K562 cells undergoing PMA-induced differentiation into megakaryocytes. PMA-induced differentiation in these cells recapitulates steps of megakaryopoiesis including gene activation, expression of CD41/61 and CD61 platelet surface markers and accumulation of intracellular reactive oxygen species (ROS). Our results show differentiating megakaryocyte cells to support higher viral replication without any apparent increase in virus entry. Further, Dengue replication suppresses the accumulation of ROS in differentiating cells, probably by only augmenting the activity of the transcription factor NFE2L2 without influencing the expression of the coding gene. Interestingly pharmacological modulation of NFE2L2 activity showed a simultaneous but opposite effect on intracellular ROS and virus replication suggesting the former to have an inhibitory effect on the later. Also cells that differentiated while supporting intracellular virus replication showed reduced level of surface marker compared to uninfected differentiated cells.